Dental Implants in Patients With Osteoporosis: A Clinical Reality? - Gaetti-Jardim, Ellen Cristina [UNESP]; Santiago-Junior, Joel Ferreira [UNESP]; Goiato, Marcelo Coelho [UNESP]; Pellizer, Eduardo Piza [UNESP]; Magro Filho, Osvaldo [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (Lippincott Williams & Wilkins, 2011)
Osteoporosis is a systemic disorder characterized by generalized decrease in bone mineral density. Dental implantology is a specialty with high predictability when both quantity and quality of the bone are respected. Therefore, the diagnosis and the implant treatment in patients with osteoporosis are important. In the current study, a literature review about osteoporosis and dental implant therapy was conducted. PubMed, Cochrane, ISI, Dentistry Oral Science, SciELO, and Bireme databases were consulted over the last 20 years. English- and Portuguese-language articles were included in this revision. Some authors stated that the osteoporotic bone is similar to the proposed model of bone type IV. Randomized clinical studies reported implant failure in patients with osteoporosis after menopause. Studies that contraindicate the use of implants in patients with osteoporosis infer that the impaired bone metabolism led to reduction of bone healing around the implants. Nevertheless, other authors believe that the presence of osteoporosis is not a definitive condition to contraindicate the therapy with dental implants. In these cases, the dentist should perform a proper treatment planning, modifying the implant geometry, and use larger implant diameter and with surface treatment. Thus, osteoporosis is not a contraindication for implant surgery because an accurate analysis of bone quality by means tomography is performed.
Keywords: Osteoporosis; diagnosis; implantology